-(7y+5)-(6y-7)=-6

Simple and best practice solution for -(7y+5)-(6y-7)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7y+5)-(6y-7)=-6 equation:


Simplifying
-1(7y + 5) + -1(6y + -7) = -6

Reorder the terms:
-1(5 + 7y) + -1(6y + -7) = -6
(5 * -1 + 7y * -1) + -1(6y + -7) = -6
(-5 + -7y) + -1(6y + -7) = -6

Reorder the terms:
-5 + -7y + -1(-7 + 6y) = -6
-5 + -7y + (-7 * -1 + 6y * -1) = -6
-5 + -7y + (7 + -6y) = -6

Reorder the terms:
-5 + 7 + -7y + -6y = -6

Combine like terms: -5 + 7 = 2
2 + -7y + -6y = -6

Combine like terms: -7y + -6y = -13y
2 + -13y = -6

Solving
2 + -13y = -6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -13y = -6 + -2

Combine like terms: 2 + -2 = 0
0 + -13y = -6 + -2
-13y = -6 + -2

Combine like terms: -6 + -2 = -8
-13y = -8

Divide each side by '-13'.
y = 0.6153846154

Simplifying
y = 0.6153846154

See similar equations:

| 13x+7-4=12x-3 | | (1+2i)+(3+7i)-2(1-i)= | | 120=w+4 | | 45a^3d-75a^2d^2-30ad^3= | | 3a+1.50(268-a)=2084 | | 3a+1.50(216-a)=888 | | (3a+5)(2a-7)= | | -6x^2+8=0 | | x^3-8x-9= | | b^2-7b-44= | | 8+2r-7=6r+1-2r | | 120=8+2w | | x^2-41x+42=0 | | 27a^3-64b^3=0 | | 6(3+n)=5(n+1) | | 12x^2+xy+6y^2=0 | | 7x^3-2x^4+45x^2-184x=-80 | | 2y+17y=114 | | 1250=1000+25(x) | | 19m=16-13m | | x/17=-5 | | 5a+3(216-a)=888 | | -9.3x=46.5 | | 784=4*f | | 21a^2+11a-2=0 | | -7(4b+4)+(29b-4)=0 | | 2.4q-2.5-4.4q=-3q-5.5 | | X-18=-x^2+2 | | 12x+a=4(3x-8) | | 1550=1000+25(x) | | n+9=m | | 2x-2=-3x-3 |

Equations solver categories